Edukasi Manajemen Stres bagi Lansia untuk Mendukung Kesehatan Mental di Pasar Minggu - Rita Komalasari; Siti Maulidya Sari; Intan Farida Yasmin; Liko Maryudhiyanto; Sri Rahayu Ningsih (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
Mental health is an important component in realizing healthy ageing, so promotional efforts are needed through health education at the community level. This community service aims to increase the knowledge of the elderly about stress management and evaluate changes in knowledge after education in East Pejaten Village, Pasar Minggu District, South Jakarta. The activity was carried out on May 11, 2026 by involving 37 elderly people consisting of 9 men (24.3%) and 28 women (75.7%). Methods include coordination with partners, pre-test, delivery of material by psychiatrists through interactive lectures, discussions, demonstrations, as well as deep breathing relaxation practices, mindfulness, and adaptive coping strategies  supported by educational posters. The evaluation was carried out using pre-test and post-test instruments containing 10 questions, then analyzed descriptively and using the Wilcoxon Signed Rank Test. The results showed that the average knowledge score increased from 91.89 to 92.97 with a difference of 1.08 points. A total of 86.5% of participants maintained the same score, 5.4% experienced an increase, and 8.1% experienced a decrease in score. Wilcoxon's test showed that the difference was not statistically significant (p=0.680). Nevertheless, this activity strengthened participants' knowledge about mental health and stress management and showed that community-based education with the involvement of psychiatrists and poster media has the potential to be a promotive strategy that supports improving the quality of life and health services for the elderly in the community.